Tantangan dan Strategi Penanganan Ketidaklengkapan Data Surat Tanda Registrasi perawat Dirumah Sakit Muhammadiyah Bandung - Himawan, Husain Abdillah; Ariyani, Nurul Dwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This study shows that the main challenges include data input errors, nurses' non- compliance in renewing their STRs, and the lack of an integrated monitoring system. Proposed strategies include increased training for nurses and administrative staff on the importance of complete registration data, implementation of an integrated health management information system, and development of policies that encourage nurses' compliance in regularly renewing STRs. In addition, better coordination between hospitals and related institutions is needed to ensure the accuracy and validity of STR data. By implementing this strategy, it is expected that incomplete STR data can be minimized, improving the effectiveness of nurse management and the quality of health services at Muhammadiyah Bandung Hospital. This research uses quantitative methods, while data collection is by means of surveys and interviews with HRD at Muhammadiyah Bandung Hospital. In this study the authors found problems in terms of nurse STRs: (1) Non-compliance of nurses in extending STR (2) Lack of policy updates at the Bandung Muhammadiyah Hospital (3) Administrative staff have difficulty verifying data. Based on the problems that occur above, the researcher tries to provide some suggestions as follows: (1) The hospital must emphasize to nurses to always pay attention to whether the STR is still active or not, if they are still indifferent, give administrative sanctions (2) The hospital must always follow the government regulations of Law No. 17 of 2023 concerning Health, namely regarding nurses must have a lifetime STR (3) The data provided by nurses for 50% STR is almost close to expiration, as in point 2, the hospital should implement and emphasize to all nurses to have a lifetime STR so as not to hamper administrative staff in verifying nurse data.